Making sense(s) in dementia: a multisensory and motor-based group activity program - Cruz, Joana (2013)
Lack of engagement in meaningful activities is associated with poor quality of life in dementia; thus, the development of these activities has been recommended. This pilot study aimed to develop a multisensory and motor-based group activity program for residents with dementia and assess its impact on residents’ behavior. The program was designed using a multisensory and motor-based approach in sixteen 45-minute weekly sessions tailored to residents’ characteristics. Four residents with advanced dementia participated in the program. The frequency and duration of the residents’ behavior were assessed using video recordings. All residents participated in the proposed activities, although they were more participative and communicative in some sessions than in others. Group activity programs based on multisensory and motor stimulation can be a promising approach for people with advanced dementia; however, further research is needed. This study may serve as reference to the implementation of future programs aiming to increase person-centeredness of the care provided.